Tronc : valuing the future of newspapers - Rosenthal, Jean W., 1945-; Tookes, Heather E.; Elias, Jaan (London : Yale School of Management, 2018)
May 2016, the Tribune Publishing board rejected a second all-cash buyout offer from Gannett Publishing, $15/share, up from an initial unsolicited bid of $12.25. The debate became public and heated, as Gannett made an appeal directly to the Tribune's non-management shareholders. The negotiations ultimately failed, but the underlying questions remained. Should the Board have accepted Tribune's offer? What was the right price? What is the best way to value a company like tronc? What might other players do next?
Originally published in Rosenthal, J., Tookes, H. E., & Elias, J. (2017). Tronc: Valuing the future of newspapers. 17-015. New Haven, CT: Yale School of Management, Yale University. Retrieved from: https://vol11.cases.som.yale.edu/tronc.
Description based on XML content.
Keywords: elektronické knihy; electronic books; Tronc; Gannett Publishing Co; Consolidation and merger of corporations